2010
DOI: 10.1007/s11270-009-0284-5
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Contents and Distribution in Coastal Sediments of the Gulf of Trieste (Northern Adriatic Sea, Italy)

Abstract: A set of ten heavy metals (Al, As, Cd, Cr, Cu, Hg, Ni, Pb, V, and Zn) was investigated in surface sediments (0-5 cm) collected in 21 sites of the Gulf of Trieste, Northern Adriatic Sea (Italy). The aim of this work was to obtain a preliminary assessment about the levels and spatial distribution of these selected elements. Ancillary parameters such as grain size, total organic carbon, and total nitrogen were also determined. The enrichment factor was calculated to discriminate if a natural condition or a stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 47 publications
4
17
1
3
Order By: Relevance
“…On the contrary, the positive correlation of TOC with sand which occurred at Ser station probably indicates that in this case, the sandy sediments convey the organic residue probably derived from the human activity of the sewage carried out by the pipeline. Mean values of 1.42% at Res station were comparable with data from Acquavita et al (2010), but slightly higher than data reported for the Slovenian sector (Faganeli et al, 1991;Covelli & Fontolan, 1997;Acquavita et al, 2010). In all cases, C/N molar ratio was always > 10, indicating that the organic matter is a mixed composition of marine and terrestrial organic compounds (e.g.…”
Section: Environmental Conditionssupporting
confidence: 84%
See 1 more Smart Citation
“…On the contrary, the positive correlation of TOC with sand which occurred at Ser station probably indicates that in this case, the sandy sediments convey the organic residue probably derived from the human activity of the sewage carried out by the pipeline. Mean values of 1.42% at Res station were comparable with data from Acquavita et al (2010), but slightly higher than data reported for the Slovenian sector (Faganeli et al, 1991;Covelli & Fontolan, 1997;Acquavita et al, 2010). In all cases, C/N molar ratio was always > 10, indicating that the organic matter is a mixed composition of marine and terrestrial organic compounds (e.g.…”
Section: Environmental Conditionssupporting
confidence: 84%
“…Grain-size demonstrates that sediments from Ser station (from 15 to 45%) were always richer in sand than Res station. The relatively high occurrence of sand at Ser station differs with the sediment distribution proposed by Brambati et al (1983), Ogorelec et al (1991) and Acquavita et al (2010) for the GoT. These authors indicated high sand content along beaches, in proximity to the Marano and Grado lagoon outlet and in the western open sector of the Gulf and clayey silt for the studied area.…”
Section: Environmental Conditionscontrasting
confidence: 72%
“…Seawater contains between 1.5 and 4.25 µg·L −1 arsenic [ 6 ], somewhat more than the average arsenic level in seawater (1.7 µg·L −1 ) [ 7 ]. Concentrations of arsenic in sediments range between 2.9–37 µg·g −1 dry weight (d.w.) [ 8 , 9 ], confirmed by own recent data (7.5–12.6 µg·g −1 , [ 6 ]). Arsenic in sea water is normally present in the inorganic forms arsenite (As(III)) or arsenate (As(V)), depending on redox conditions.…”
Section: Introductionsupporting
confidence: 77%
“…However, where some elements exceed the environmental quality standards (EQS) set by the WFD it should be stressed that these represent, similarly to what reported for the adjacent Gulf of Trieste (Acquavita et al, 2010b), the values underlying the region's natural lagoon geochemistry.…”
Section: Manila Clam (Tapes Philippinarum Adams and Reeve 1852) In Thementioning
confidence: 71%